Pattern of clinicopathological parameters of cats with lower urinary tract diseases presented to University Veterinary Hospital, UPM - Siti Aisyah Jeinie @ Jamal. (2017)
Feline Lower Urinary Tract Disease (FLUTD) is among the most common diseases reported in cats in various countries globally. A retrospective cohort study was conducted based on 173 FLUTD cases recorded in 2016 at the Clinical Pathology Laboratory, Faculty of Veterinary Medicine, UPM and followed by examination of the case profiles at the University Veterinary Hospital, UPM. Data collected included patient signalments, haematological, serum biochemical and urinalysis result. The specific risk parameters were age, breed, sex, lifestyle, diet, weight, clinical signs, leukogram (white blood cells (WBC) count), serum biochemistry (globulin, urea and creatinine levels) and urinalysis (pH, haematuria, proteinuria, pyuria, and bacteriuria) which were analysed using SPSS 22.0 software program. Results showed that Domestic Short Hair (DSH) male cat, weighing 3.00-3.99 kg with average body condition score (BCS) of 3, living indoor in a multicat household and aeting non-prescription dry feed made up the significant attributes of the most common profile of FLUTD cases. The common clinical signs were stranguria (42.2%), haematuria (38.7%), turgid urinary bladder (37%), non-compressible urinary bladder (28.9%) and vomiting (28.3%). From the 173 cases, 124 cases ordered haematological analysis whereby 32.4% had normal leukogram, while 15% had mild hyperglobulinaemia. Urinalysis showed severe haematuria with trace to mild pyuria, moderate proteinuria, and mild bacteriuria. The most common diagnosis was bacterial cystitis. In FLUTD management, the important risk factors of higher concerns include male cats living indoor in a multicat household fed with dry non-prescription diet.